Hydrogen Peroxide Senzing By Dichalkogenide Quantum Dots Prepared By Lpe - Zahradníček, Radim (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2019)
Signalling molecules such as hydrogen peroxide (H2O2) play crucial role in cellular metabolism. Under pathological conditions, the cell is unable to control enzymatic conversion H2O2 into water and oxygen. This fail in cell metabolism could lead to damage of cell. Thus produced H2O2 is presented at a nanomolar scale and currently there is a lack of suitable electrochemical sensors for its sensitive detection. Modification of screen printed electrodes (SPE) with 2D-nanomaterial quantum dots prepared by Liquid Phase Exfoliation (LPE). MoS2, MoSe2, WS2 and WSe2 compounds were used for this purpose. Such modified electrodes were characterized and optimized for hydrogen peroxide detection.
Keywords: quantum dots; dichalcogenides; lpe; hydrogen peroxide; sensing; screen printed electrodes